9x+3x+9x=6+8x+11

Simple and best practice solution for 9x+3x+9x=6+8x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+3x+9x=6+8x+11 equation:



9x+3x+9x=6+8x+11
We move all terms to the left:
9x+3x+9x-(6+8x+11)=0
We add all the numbers together, and all the variables
9x+3x+9x-(8x+17)=0
We add all the numbers together, and all the variables
21x-(8x+17)=0
We get rid of parentheses
21x-8x-17=0
We add all the numbers together, and all the variables
13x-17=0
We move all terms containing x to the left, all other terms to the right
13x=17
x=17/13
x=1+4/13

See similar equations:

| 0.25(3x-8)=2(0.5x+4 | | 2x+(3x+13)=108 | | 6a-14=5a | | 0=64-t-5t^2 | | 9/5c+32=41 | | -15x+4=2x+81 | | 41=9/5c+32 | | (130-7x)=(20+3x) | | 5x-3x=5-2 | | 59+2x=115 | | 628+124m=1504 | | Y=7x-290 | | (6x+1)/(2x-1)=5 | | (7+2x)/2=5 | | 4-3(p+2)=2(p-4) | | 5x+3x=5-2 | | x+88=121 | | k.12=-5k-3 | | -8x+2=28 | | (6x+1)/(2x-1)=9 | | 0.5(5-7x=8-1(4x+6) | | 4+3(w-9)=-12 | | P(x)=-6x-9 | | 5x+3x=2+5 | | 7x−9=4x | | 43+8p=p+21 | | 2x+45=87 | | 13+2a=3a-14+24 | | 14v+50=2(5v+29) | | 420(2r+10=) | | -w+66=2w | | 8x=x2+15 |

Equations solver categories